Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jfmk6020052
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Exercise Capacity and Training Prescription from the 6-Minute Walk Test and Rating of Perceived Exertion

Abstract: Walking tests, such as the 6-min walk test (6MWT), are popular methods of estimating peak oxygen uptake (VO2peak) in clinical populations. However, the strength of the distance vs. VO2peak relationship is not strong, and there are no equations for estimating ventilatory threshold (VT), which is important for training prescription and prognosis. Since the 6MWT is often limited by walking mechanics, prediction equations that include simple additional predictors, such as the terminal rating of perceived exertion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, in the majority of Australian cardiac rehabilitation programs, distance-based field testing protocols, such as the six-minute walk test or the incremental shuttle walk test, are the preferred option [7]. Recent research has shown that the addition of final RPE to six-minute walk test distance can improve the estimation of CRF [44]. The use of this methodology by Australian programs may assist clinicians to provide patients with a more precise exercise prescription.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the majority of Australian cardiac rehabilitation programs, distance-based field testing protocols, such as the six-minute walk test or the incremental shuttle walk test, are the preferred option [7]. Recent research has shown that the addition of final RPE to six-minute walk test distance can improve the estimation of CRF [44]. The use of this methodology by Australian programs may assist clinicians to provide patients with a more precise exercise prescription.…”
Section: Discussionmentioning
confidence: 99%
“…If the cardiopulmonary test is not available, a 6-min walking test associated with the terminal evaluation of perceived effort using the Borg scale is a useful tool for the clinician in prescribing exercise. 20 , 21 Subsequent check-ups should be based on the evaluation of the patient’s adherence to the prescribed exercise plan and they should include a brief motivational interview and a complete functional assessment to quantify progresses and readjust the exercise plan based on the needs.…”
Section: Step 3: Treatment Targets and Implementation Of Healthy Beha...mentioning
confidence: 99%
“…Nevertheless, the sensitivity of estimated CRF is highest when maximal exertion (or near maximal, e.g., >85% age-predicted heart rate maximum and/or >17 on a 20 point Borg Rating of Perceived Exertion scale) is achieved, particularly when comparing repeated assessments (e.g., change in CRF) among populations. Several submaximal tests of CRF have been used in clinical and Shorter timed walk tests, such as the 400 meter and 6-minute walk, are readily used in clinical and epidemiological settings to assess physical function status as well as to predict V O 2max with reasonably high accuracy when compared against directly measured V O 2max (e.g., R 2 = 0.71-0.76; SEE <1.5 METs) [35,36]. The choice of performance-based test to assess CRF will depend on available equipment and testing personnel, population being studied, participant burden and safety, and time and budget constraints.…”
Section: Measuring Cardiorespiratory Fitnessmentioning
confidence: 99%